Genetic diversity of local sweet potato cultivars (Ipomoea batatas [L.] Lam.) from Bulungan, North Kalimantan based on morphological characters - OKTAVIANINGSIH, LINDA; FITRIANI, FITRIANI; HENDRA, MEDI; ARIF, MUHAMMAD FAUZI (Jurnal Natural, 2024)
Indonesia is one of the centers of sweet potato diversity worldwide. Sweet potatoes have the potential to be developed for food consumption. This research aims to determine the diversity of sweet potato cultivars, their morphological characteristics, and the relationships between local sweet potato cultivars in Bulungan Regency, North Kalimantan. The local sweet potato cultivars were selected using purposive sampling with the exploration method. The morphological characterization of the samples is based on IBPGR (International Board for Plant Genetic Resources) standards. Cluster analysis was conducted to identify the relationships using MVSP software version 3.1. The research identified 27 local sweet potato cultivars in Bulungan Regency. Morphological characterization revealed 41 characters that can differentiate each local sweet potato cultivar. The most influential characteristics include leaf shape, flower surface texture, the position of the stigma, flower surface color, back petal color, center shape and the number of lobes, primary leaf vein color, lobe type, main leaf bone color, stem internode length, and plant type. A flower shape that had not been discovered before, a pentagonal shape with curves, was identified. Cluster analysis divided the cultivars into two major groups with a coefficient range of 0.593 to 0.888 (59.3 to 88.8%). Cluster A consisted of one member, LK-7 (purple sweet potato), while Cluster B consisted of several subgroups with 26 local cultivars. The people of Bulungan Regency use these local cultivars for food, animal feed, and medicinal purposes.